Analisis Kemampuan Pemecahan Masalah Siswa SMP dalam Menyelesaikan Soal Pada Materi Aritmatika Sosial - Fitrie Andayani; Adiska Nadiyah Lathifah (Mathematics Education Study Program, 2019)
The purposes of this research is to analyze the problem solving ability of student junior high school in solving social arithmetic test, the ability that hoped might by students is solving math test ability with good and true. Budiman states that fourt steps for solving the test, that are: identify sufficiency of data to solving the problem, make the model of math from any problem, pick and apply strategy for solving the problem, and then check the true of the result or the answer. The subjeck of this research is eighth grade of SMPN 3 CIMAHI that there are 36 students. The instrument that used by this study are test and interview. This study used qualitative descriptive method. Based on the analyze the data can concluded that the mistake that made by a lot of students is on the indicator understanding the problem. Student can not understand the question on social arithmetic material. On the made the math model indicator, pick the strategy of solving, problem solving, and check the result of the answer back just as student who can do on this step.